FUZZY C-MEANS CLUSTERING UNTUK PENGELOMPOKAN BAHAN MAKANAN BERDASARKAN KANDUNGAN ZAT GIZI - Meysi Budiyanti; Mutia Nur Estri (Universitas Jenderal Soedirman, 2012)
Fuzzy C-Means Clustering (FCM) is a data clustering technique where each data point belongs to a cluster by membership degree. FCM starts with the concept of cluster centers that mark the mean location of each cluster. By iteratively updating the cluster centers and the membership degree for each data point, then the cluster centers move to the right location. FCM can be applied to group the nutrients of foods based on three functions of nutrients which are food as energy provider, body functions regulator and growth developer. Each nutrients are grouped into three cluster. The information of food group can used as reference or recomendation for someone who